Identifikasi Penyebab Kerusakan Produk Karet SIR 20 Dengan Menggunakan Metode Failure Mode And Effect Analysis (FMEA) - Wibowo, Heri; Khikmawati , Emy; Setiawati, Indah (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2020)
PT. Perkebunan Nusantara VII Lampung is an industrial company that processes rubber processed materials into the rubber of type SIR 20. The problem that occurs with this type of product is that the PO content does not comply with predetermined quality standards. The purpose of this study is to analyze the causes of product damage using the Failure Mode and Effect Analysis (FMEA) method, to obtain the greatest risk of failure in the production process in the value of the Risk Priority Number (RPN), and to provide recommendations for its improvement. The results of the data collection analysis are described through a Check Sheet Diagram to determine the damage from several rubber data samples of the SIR 20 type, then described the Cause Failure Mode Effect (CFME) to determine the factors that cause damage to PO levels originating from human, material and work environment factors. After that, describes the FMEA analysis to determine the RPN value, where the highest RPN value is the different rubber freezers, loud engine sounds and vibrations, and the operator's lack of accuracy in regulating the temperature of the dryer. The recommended improvement proposal is to receive good quality raw materials and increase the price of raw materials, as well as provide guidance to farmers about good types of rubber freezers, requiring the use of earplugs so that machine noises do not interfere with the operator's work, providing training and warning to operators not to make mistakes, and carry out intensive inspections of operators.